Profile of elementary school teachers of a public network about learning disabilities - Andréa Carla Machado; Karina Kelly Borges; Maria da Piedade Resende da Costa; Maria Amelia Almeida (Universidade Federal de Santa Maria (UFSM), 2015)
This study set out to identify the knowledge of him who acts directly with the student, the teacher, so consider it an important character in the process of identifying students with learning disabilities. So the goal was to verify and analyze the knowledge of the professor regarding the learning disorder. To meet the goal, it was applied a questionnaire with open and closed questions in 78 teachers of both genders with a predominance of the female, with an average age of 35 years and 7 months belonging to a public elementary school in a medium-sized town in the State of São Paulo in Brazil. In the analysis it was observed three groups of teachers, those who have knowledge, those who have partial knowledge, and those who are not aware of the matter. Becomes of utmost importance taking place training projects for teachers reading, where they discuss their affective attitudes, personal experiences and pedagogical, the conceptions that he has on the learning disabilities, their characteristics, so that they can motivate students to learn.